No Continuing City, or the City to Come? Observations on Parliament and its Library. Issue 1 (2nd January 2017) - Cope, R. L.
Abstract: This essay asks why the 175th anniversary in 2015 of the NSW Parliamentary Library received so little public or professional attention. This puzzling lack of awareness contrasts sharply with the year-long celebrations in 1990, commemorating the Library's sesquicentenary. In assessing this observation, the essay notes that the field of parliamentary librarianship has suffered a noticeable eclipse in recent years here and abroad. The parliamentary institution itself is also experiencing a severe drop in public confidence. Attention is paid to the significance of the Commonwealth Parliamentary Library whose role is paramount in the Australian parliamentary context. The role of the state parliamentary libraries is then reviewed. The importance and fate of their collections, deemed by some to be heritage collections of the nation, is discussed. Factors underlying the decline of the state parliamentary libraries are then considered and some international parallels are drawn. In light of the decline of the state parliamentary libraries, the controversial question of whether the state parliaments have the requisite will and infrastructure to offer continuing support to their libraries is canvassed. Metaphorically we ask: do the libraries constitute a non-continuing city? What kind of library service is realistic in parliaments in the twenty-first century where the presence of the digital age is now recognised? Is there a new city needed to replace them?